DAMPAK KEBIJAKAN SERTIFIKASI GURU TERHADAP PENINGKATAN PROFESIONALISME GURU (STUDI KASUS SDN 037 KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU TAHUN 2009-2011) - Imelda Fitra; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research is motivated holding this teacher certification program for public elementary school educators see the persistence of the low educational qualifications for teacher certification policies that educators must diploma 4 (D4) or better known as the stratum 1 (S1) such regulations have been written The Law of the Republic of Indonesia No. 14 Year 2005 on Teachers and Lecturers.The purpose of this study was to determine why the impact of teacher certification policies have not been able to improve the professionalism of teachers in 037 villages sdn new intersection subdistrict pekanbaru handsome city and to determine the factors that affect the impact of teacher policy in the professionalism of teachers in 037 villages sdn new intersection handsome city subdistrict pekanbaru. The usefulness of the research is the primary school teachers to prepare for certification by further improving academic qualifications and professional competence, pedagogical, social, and personality.Types and methods of research is the type qualitative. Qualitative stages through the various stages of critical-scientific thinking, which the researchers begin to think inductively, which captures various facts and phenomena through observation in the field. Researchers use qualitative research Presentation of data in the form of a narrative, in-depth stories, or detail of the respondents of the interview. The results showed since their teacher policies towards the professionalism of teachers in 037 villages sdn new intersection handsome city subdistrict concluded pekanbaru has little able to improve the professionalism of teachers, and the factors that influence the Teacher Certification Policy Against Increasing Teacher Professionalism is the educational qualification, the principal policy, welfare of teachers, physical environment, and mindset.keywords: Impact, Policy, Teacher Certification, Professional Teacher